The effect of operating parameters on the wear behaviour of disc poppet valves in reciprocating slurry pumps - Joffe,S.H.D (Centre for Materials Engineering, 2016)
An investigation has been carried out to determine the factors controlling the wear characteristics of disc poppet valves in reciprocating slurry pumps used in the transportation of quartzite slurries. A laboratory test rig has been designed and built which closely simulates the operating conditions experienced by slurry pump valves. Experiments have been conducted to determine the effect of the design parameters, namely - slurry constitution, valve closure velocity and valve angle, on the wear resistance of a low alloy steel, as a function of its mechanical properties. It has been shown that the wear of the valves is a sensitive function of the operating parameters. Significant improvements in the life of the valves can be achieved through increasing material hardness, reducing valve closure velocity, slurry density and valve angle. A detailed study has been made of the mechanisms contributing to valve wear. It has been established that both percussive impact and three body abrasion wear mechanisms predominate. The influence of each mechanism has been shown to be a function of the slurry constitution and the material hardness.